Assessing Intra- and Inter-Analyzer Imprecision in Automated Hematological Laboratories: Imprecision of hematological analyzers - Pighi, Laura; Tosi, Marco; Rizza, Mariateresa; Salvagno, Gian Luca; Lippi, Giuseppe (Journal of Medical Biochemistry, 2025)
Background: Reliable hematology results are crucial for patient diagnosis and monitoring. Maintaining low variability is particularly important for key parameters like hemoglobin, white blood cells, and platelets, especially in automated laboratory workflows where multiple hematological analyzer are connected within the same line.Methods: Two residual whole blood samples, one normal and one pathological, were analyzed in ten consecutive replicates on a Sysmex XN-10 analyzer (XN‑1) and then on a second connected analyzer (XN‑2). Intra-analyzer and inter-analyzer imprecision were calculated as coefficients of variation (CV%).Results: Intra-analyzer CVs for the normal sample ranged from 0.3% for hemoglobin to 1.5% white blood cells, while inter-analyzer CVs remained below 2%. For the pathological sample, intra-analyzer CVs were 0.3–1.0%, and inter-analyzer CVs reached up to 2.1% for hematocrit and platelets. Red blood cells count, mean corpuscular volume and neutrophils showed CVs
Keywords: Laboratory hematology; Automation; Imprecision